Selection of the most suitable distribution channel using fuzzy analytic hierarchy process in Turkey - (:unkn) unknown (Inderscience Publishers, 2008)
The supplier evaluation and selection system are an important problem that can significantly affect the future competitiveness and the performance of an organisation in logistic sector. The distribution channel type has an effect on the supplier performance. This paper presents a comprehensive hierarchical structure for selecting the right distribution channel. The structure can systematically build the goals of the most suitable distribution channel selection to carry out the business goals and strategies of an organisation and a logistic firm. In this paper, fuzzy Analytic Hierarchy Process (AHP) based methodology is discussed to tackle the different decision criteria like risk factors, cost and quality. Saaty's AHP method was developed with fuzzy logic to assist in multi-criteria decision making problems. The implementation of the system is demonstrated by a problem having four stages of hierarchy which contains different criteria and attributes. The model is explained by an illustrative example. © 2008, Inderscience Publishers.
Keywords: Distribution channels; Fuzzy AHP; Logistics; Turkey